Benefits of multi-micronutrient nutritional formula combined with aerobic exercise on children with attention deficit hyperactivity disorder: improvements in symptoms, cognition, executive function, and sleep - Ye, Yanjuan; Wang, Yun (Frontiers in Pediatrics, 2025)
ObjectivesAttention-Deficit/Hyperactivity Disorder (ADHD) affects approximately 5% of children globally and is characterized by symptoms of inattention, hyperactivity, and impulsivity. This study examines the impact of a multi-micronutrient nutritional formula combined with aerobic exercise on ADHD symptoms, cognitive function, specifically the domain of executive function, and sleep quality.MethodsA retrospective analysis was conducted on 220 children aged 6–12 years diagnosed with ADHD according to the American Psychiatric Association (APA) guidelines, who had been treated at WuXi No.2 People's Hospital from November 2022 to October 2024. Participants were divided into two groups: the Multi-Micronutrient Nutritional Formula (MNF) group (n = 111) who received a three-month dietary supplementation and a MNF combined with Aerobic Exercise (MNF-AE) group (n = 109) who received both the nutritional formula and daily aerobic exercise. Evaluations included the Conners Parent Symptom Questionnaire (PSQ), Stroop Test, Wisconsin Card Sorting Test (WCST), Alternate Uses Task, and the Children's Sleep Habits Questionnaire (CSHQ).ResultsPost-treatment, the MNF-AE group exhibited significant improvements in ADHD symptoms, demonstrated by reduced PSQ scores (mean 30.75 ± 3.87) compared to the MNF group (32.42 ± 4.17; P = 0.002). The MNF-AE group also showed enhanced cognitive processing speed and selective attention, evidenced by faster Stroop Test times (Stroop Word: 23.03 ± 7.53 s vs. 25.86 ± 5.37 s; P = 0.002). Executive function improved significantly, as evidenced by higher total correct scores in the WCST (76.98 ± 10.74 vs. 73.75 ± 12.44; P = 0.041) and creativity (assessed by the Alternate Uses Task) improved in originality and fluency (all P < 0.05). Moreover, the MNF-AE group had better overall sleep quality as indicated by lower CSHQ scores (72.63 ± 6.87 vs. 74.95 ± 6.22; P = 0.009).ConclusionsCombining multi-micronutrient supplementation with aerobic exercise may offer potential benefits for managing ADHD symptoms, improving cognitive function, as well as enhancing sleep quality in children with ADHD. These findings suggest potential additive effects of this combined intervention.